A balance between candidate- and party-centric representation under mixed-member systems: The evidence from voter behavior in Taiwan. (October 2017) - Tsai, Tsung-han
Abstract: Mixed-member systems are usually defined as electoral systems that combine SMDP and CLPR, both of which are more likely to induce party reputation-seeking. Building on the literature of electoral institutions, this article provides an explanation of how mixed-member systems structure voter behavior and achieve a balance between candidate- and party-centric representation. Using Taiwan as a case of MMS, this article tests hypotheses against survey data and investigates the determinants of voting decisions for the two ballots. By employing a Bayesian bivariate probit model, this article shows that, first, partisan factors affect voter behavior in both nominal and list ballots. However, it is affective rather than rational considerations for political parties that play the major role. Second, personal reputation influences voters' choices of the nominal and list vote, but only negative elements matter for the list vote. Finally, there is a moderately positive correlation between the two ballots, which potentially results from affective, partisan considerations.